HIV Prevention Behavior On SMK Negeri Student In South Central Timor District 2019 - Bahan, Roni Lorensus; Manurung, Imelda F.E; Sir, Amelya B (Timorese Journal of Public Health, 2020)
HIV/AIDS is an infectious disease that has been identified as current global health problem. HIV is more prevalent in people of adolescent age as they more likely to engage in high-risk sexual behaviours. Research has found that transmission of HIV among adolescents can be prevented through education and availability of correct information about the disease. The purpose of this study is to assess HIV prevention practices of students in State Vocational Schools in South Central Timor Regency in 2019. The research used a combination of descriptive and qualitative methodologies. This sample population for this study was 878 students in the “Class XII”. Sampling was conducted using a random sampling technique and as many as 288 students were interviewed. The data was analysed using a univariate analysis. This was done in order to get a picture of the distribution of respondents in the forms of percentages and tables. The results of the study illustrated the HIV prevention behavior of vocational high school students in South Central Timor Regency were the good majority as many as 241 respondents (83.68%), the description of the knowledge of vocational students in South Central Timor Regency were the majority of less knowledge as many as 264 respondents (91.66%), The description attitudes of SMKN students in South Central Timor Regency was the majority that have positive attitudes as many as 160 respondents (55.55%), the description of information exposure of SMKN students in South Central Timor Regency was the majority that have good information exposure of 270 respondents (93.75%). In conclusion, disseminating information through media in way that is easy for student to understand is an effective way to increase students' knowledge about HIV prevention practices.